Subject integration of physical education and English as a means of enriching modern lesson content (Pedagogy of Higher and Secondary Education, 2015)
Kadchenko L. P., Marchyk V. I. Subject integration of physical education and English as a means of enriching modern lesson content.The article deals with an integrated approach in teaching. The possibility of a harmonious combination of physical culture and foreign language is examined. The reasonability of conducting the integrated lessons of physical culture and English and the ways of implementation of an integrated approach in the organization of sports activities and physical education lessons in a foreign language are substantiated.
Keywords: subject integration; integrated approach; integrated learning; physical activity break; command